Case Report: Treatment of Alectinib in NSCLC With Brain Metastasis Patient Refractory to Radiotherapy After Resistance to Crizotinib - Zhang, Chunzhi (Frontiers in Oncology, 2021)
Background: Brain metastasis is the most common form of tumor recurrence after resistance to crizotinib in patients with anaplastic lymphoma kinase (ALK)-positive non-small-cell lung cancer (NSCLC). The treatment of brain metastasis in patients with ALK-positive NSCLC requires a multidisciplinary approach, including targeted therapy, chemotherapy, and radiotherapy. At present, no optimal treatment for these patients has been identified, although radiotherapy has remained a vital treatment. Case presentation: We experienced a patient with ALK-positive NSCLC who developed brain metastasis after crizotinib therapy. ALK rearrangement was not detected in a blood sample using next-generation sequencing. In accordance with National Comprehensive Cancer Network guidance, the patient underwent whole-brain radiotherapy. However, the number of metastatic sites unexpectedly increased. In desperation, the patient was empirically given alectinib after radiotherapy failure, and unanticipated success was achieved. Conclusions: This case revealed some new insights. First, liquid biopsy is complementary to tissue biopsy in patients with NSCLC, mainly in those with EGFR mutation. However, ALK rearrangement should be assessed using tissue biopsy as much as possible. Second, brain metastasis of NSCLC might respond to second-generation tyrosine kinase inhibitors (TKIs), such as alectinib and ceritinib, after resistance to crizotinib regardless of the presence or absence of ALK rearrangement in liquid biopsy. Finally, combined radiotherapy and TKI therapy appears optimal in patients with brain metastasis of NSCLC after resistance to crizotinib in the absence of a definitive driver gene.